Sonidos del fútbol bogotano: procesos de hiperculturación sonora en los hinchas durante el siglo XXI (2020)
Sonic Transculturation processes includes a general restructuring of practices, circulation and modes of signification of the sonic. From Ethnomusicological studies, is uncommon to find approaches that includes this elements and their relationships. Instead, recent literature on this topic offers partial explanations for a phenomena that should be studied as a system. Having this in mind, the aim of this project is to explain the relationship between sonic transculturation processes and the configuration of acoustic communities with soccer fans from Bogotá during the 21st century. The methodological design for this research included feedback interview techniques and due to the public health issues related to COVID-19, the fieldwork was adapted to a digital ethnography, which leaded to the configuration of the Sonic Hiperculturation concept. So far, this study shows that even when sonic transculturation determines the configuration of acoustic communities, the existence of this communities implies transnational interchanges that makes this groups permeable...